Moderate clipping stimulates over-compensatory growth of Leymus chinensis under saline-alkali stress through high allocation of biomass and nitrogen to shoots - Ma, Huimin; Zheng, Congcong; Gao, Yingzhi; Baskin, Carol C.; Sun, Hao; Yang, Haijun (Plant growth regulation, 2020)
Leymus chinensis , a dominant species in the Songnen Plain of northeast China, has a strong ability to resist grazing and tolerate saline-alkali stress. Compensatory growth is a positive response of plants, when subjected to grazing or clipping stress; however, little information is available on how plant nitrogen allocation strategies affect compensatory growth under saline-alkali stress. A field experiment using two saline-alkali levels and three clipping levels was conducted in conjunction with the belowground 15 N-urea labelling method. Irrespective of clipping and salt-alkali stress, moderate clipping significantly promoted allocation of newly-absorbed nitrogen (N) to shoots, resulting in high biomass and over-compensatory growth of L. chinensis . However, severe clipping dramatically decreased uptake of total 15 N by 20% under saline-alkali conditions, resulting in under-compensatory growth, and plants allocated more N to stem bases than to other plant organs, showing a conservative N allocation strategy. Our results suggest that plants have different nitrogen allocation strategies under different combinations of environmental stresses.